Perancangan Database dan Visualisasi Data dari Program Jumpstart pada PT. X - Jefry Djoko; Prayonne Adi (Jurnal Titra, 2021)
This research was conducted to design a database and data visualization from the Jumpstart program at PT. X. Jumpstart is a new employee orientation program at PT. X where workers perform and fill in the content according to the timeline provided by the company. The purpose of this Jumpstart program is to introduce and understand what needs can be given to new employees during the orientation process within the company. The Jumpstart program however has some problems in terms of data processing, has difficulty processing the results of responses that are processed in Google Spreadsheets. This problem can be fixed by designing a database and data visualization that processes data based on the results of these responses. The data processed in the database can be monitored in real-time by the company in accordance with the data of new workers in PT. X, this is to facilitate the flow of coordination between each party in the Jumpstart program and ensure the Jumpstart program runs well. The data that is processed in this database will be displayed in the form of data visualization to make it easier for users to draw conclusions according to the existing results. The results of this database and data visualization can help companies understand the performance of new workers in performing at Jumpstart program and also help users to follow up on areas within the companies' reach.